Reduced catecholamine response to exercise in amenorrheic athletes - Schaal, K.; van Loan, M. D.; Casazza, G. A. (Medicine & Science in Sports & Exercise, 2011)
Studies have found an array of endocrine disturbances related to energy deprivation in women with functional hypothalamic amenorrhea.